Low‐Field Nuclear Magnetic Resonance Time Domain Characterization of Polyunsaturated Fatty Acid–Rich Linseed and Fish Oil Emulsions during Thermal Air Oxidation. (1st April 2021) - Resende, Maysa T.; Linder, Charles; Wiesman, Zeev
Abstract: Linseed contains high levels of polyunsaturated fatty acids (PUFA), such as α‐linolenic acid (> 50% ALA‐18:3), that are naturally protected against thermal oxidation by their encapsulation within linseed oil bodies (OB) by multiple components including antioxidant proteins and mucilage emulsifying agents. Linseed OB emulsions (LSE) can be produced by grinding linseed seeds, adding water, adjusting pH, and sonication. This is a process that can encapsulate externally added PUFA to minimize their thermal oxidation, as it does for the intrinsic ALA PUFA. Fish oil (FO) encapsulation into this LSE platform to form linseed fish oil emulsions (LSFE) offers the possibility of a nutritive delivery system of the biologically essential FO PUFA eicosapentaenoic acid and docosahexaenoic acid. In this study, 1 H low‐field nuclear magnetic resonance (LF‐NMR) is used to characterize LSE's and LSFE's chemical and structural properties as well as their stability and changes under thermal oxidation (55 °C for 96 hours). 1 H LF‐NMR data processing was developed to generate one‐dimensional (1D) T1 (spin–lattice), 1D T2 (spin–spin), and 2D (T1 vs. T2 ) relaxation time spectra that can characterize OB emulsions and monitor their time domain fingerprints (spectrum peaks) of chemical and structural changes during the oxidation process. The 1 H LF‐NMR analysis were further supported and correlated with conventional peroxide value test, self‐diffusion, droplet size distribution, zeta potential estimation of surface stability, and gas chromatography–mass spectrometry analysis of fatty acid profile changes under thermal oxidation conditions. The 1D and 2D LF‐NMR relaxation spectra showed that the LSE and LSFE did not suffer intense oxidation process, due to PUFA assembly in OB oxidative protection. These results were further confirmed by the supportive analytical methodologies. The results of this study demonstrate the efficacy of 1 H LF‐NMR methodology to monitor PUFA's rich oil and emulsion thermal oxidation.